Discourse of civil military relations in Nepal - Bhandari, Chiranjibi; Sharma, Rajendra (Unity Journal, 2020)
A sovereign nation –state requires a strong military institution and the Nepali Army demands its personnel’s obedience, loyalty, sacrifice and discipline to maintain command and control. However, as an established principle, civilian control of the military is desirable to the military control of the state. The concept of Civil Military Relations (CMR) is dynamic, evolutionary and country specific. Such a bond between an official security organization and the public in general change with regime shifts, external imperatives and technological innovations. The impact of regime changes and political movements has been observed in various aspects of politics, society in Nepal is not an exception. In this line, this article deals on the theoretical discourse of CMR, reviews the constitutional and legal provisions and examines the factors influencing CMR in Nepal from the period of modern nationstate formation to present days. Along with existing debates around the role of the Nepali Army in various non-military jobs, this paper proposes multiple perspectives on how different entities, including bureaucrats, politicians and military leaders perceive CMR. Likewise, the writers argue that sharing the responsibilities among the civil society, citizenry and military organizations is one of the most suitable approaches in response to balancing CMR in Nepal.